2023
DOI: 10.1111/iju.15315
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen follow‐up and management for patients undergoing holmium laser enucleation of the prostate

Shingo Kimura,
Hiromichi Katayama,
Eiichiro Ohara
et al.

Abstract: ObjectivesTo investigate who needs a careful postoperative monitoring for prostate cancer (PCa) after holmium laser enucleation of the prostate (HoLEP). We examined characteristics and oncological outcomes of HoLEP‐related PCa.MethodsPatients who underwent HoLEP during 2002–2017 in a Japanese tertiary center were retrospectively analyzed. Patients were divided into non‐PCa, PCa with HoLEP specimen (PCa‐Ope), and PCa diagnosed during follow‐up (PCa‐Post). Outcomes of all HoLEP‐related PCa were monitored.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…They also reported that enucleation efficiency should be more critical than preoperative prostate volume (PV) to consider the pPSA, and lower enucleation efficiency (enucleated volume/PV) was significantly associated with pPSA >1.2 ng/mL, which is an essential perioperative finding because PSA is likely to be elevated because of residual prostate after HoLEP. 1 In other recent reports, Lambert et al demonstrated that 24 (4.2%) out of 773 patients developed postoperative PCa after HoLEP and argued that the pPSA after HoLEP is an independent predictor for future diagnosis of PCa. 2 Closer follow-up and diagnostic investigations to detect postoperative PCa are indicated when pPSA is >1.73 ng/mL (ROC AUC 0.903), specifically within the first year after HoLEP.…”
Section: Editorial Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…They also reported that enucleation efficiency should be more critical than preoperative prostate volume (PV) to consider the pPSA, and lower enucleation efficiency (enucleated volume/PV) was significantly associated with pPSA >1.2 ng/mL, which is an essential perioperative finding because PSA is likely to be elevated because of residual prostate after HoLEP. 1 In other recent reports, Lambert et al demonstrated that 24 (4.2%) out of 773 patients developed postoperative PCa after HoLEP and argued that the pPSA after HoLEP is an independent predictor for future diagnosis of PCa. 2 Closer follow-up and diagnostic investigations to detect postoperative PCa are indicated when pPSA is >1.73 ng/mL (ROC AUC 0.903), specifically within the first year after HoLEP.…”
Section: Editorial Commentmentioning
confidence: 95%
“…Meanwhile, Ishidoya et al reported that postoperative PCa could be potentially more malignant than most iPCa. 1 Late diagnosis after HoLEP can lead to a poor prognosis of pPCa; therefore, recognizing the risk of pPCa is essential.…”
Section: Editorial Commentmentioning
confidence: 99%